Genetic relatedness among Asian Cotoneaster species investigated with DNA marker analysis - Nybom, H.; Bartish, I. V.; Fryer, J. (International Journal of Horticultural Science, 2005)
The widespread genus Cotoneaster has its centre of diversity in the Himalayas and surrounding areas. Most taxa appear to be polyploid and apomictic, and many of them have become popular ornamentals due to their attractive foliage and berries. One of the taxonomically most critical groups is Section Alpigeni which contains several important ornamental plants. The number of species belonging to this section varies widely between different taxonomic treatises, depending on whether ’splitting’ or ’lumping’ of species is preferred. Using a rather narrow species definition, we have investigated 13 different species using RAPD analysis. A simple matching (SM) coefficient-based principle coordinate analysis (PCO) was calculated from the RAPD data. Some species were clearly more similar to each other than to other species in the analysis. The levels of similarity did, however, not correspond very well to the lumping together of several taxa under the same species name as performed e.g. in the recent Flora of China. Obviously, the complex hybridogenous origination and, in some cases, still ongoing recombination with sexual species or among the apomictic taxa themselves, produces a genetic variability structure that cannot be properly reflected in a hierarchical taxonomy.